2019
DOI: 10.4041/kjod.2019.49.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis of metal clips of ceramic self-ligating brackets

Abstract: ObjectiveThe aim of this study was to analyze the surface composition, roughness, and relative friction of metal clips from various ceramic self-ligating brackets.MethodsSix kinds of brackets were examined. The control group (mC) consisted of interactive metal self-ligating brackets while the experimental group (CC, EC, MA, QK, and WA) consisted of interactive ceramic self-ligating brackets. Atomic force microscopy-lateral force microscopy and scanning electron microscopy-energy-dispersive X-ray spectroscopy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This fact may be explained by the more polished, smoother surface and greater rigidity of this wire, so that in spite of the pressure exerted by the clips of the active self-ligating brackets, the contact surface of this wire would not be increased. In the case of conventional brackets, the elastic ligature would not produce sufficient force to increase the surface of contact at the bracket/archwire interface, corroborating the findings of previous studies in which the composition of the archwire and clip of the bracket were reported 2,11,16,18,19,21 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This fact may be explained by the more polished, smoother surface and greater rigidity of this wire, so that in spite of the pressure exerted by the clips of the active self-ligating brackets, the contact surface of this wire would not be increased. In the case of conventional brackets, the elastic ligature would not produce sufficient force to increase the surface of contact at the bracket/archwire interface, corroborating the findings of previous studies in which the composition of the archwire and clip of the bracket were reported 2,11,16,18,19,21 .…”
Section: Discussionsupporting
confidence: 86%
“…The frictional force may vary according to the materials used, and whether the environment is wet or dry, type of brackets, archwires and ligations. Self-ligating brackets may be divided into active and passive types; the active types have a spring clip that invades the bracket slot putting pressure on the archwire, while in the passive system, the clip does not invade the slot, it only covers the slot without putting pressure on the archwire [1][2][3][4][5]7,10,12,[14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…[17] Surface roughness of the brackets can be affected by its surface structures, such as material, coating, manufacture techniques, and the interaction between bracket and archwire. [18]…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several esthetic self-ligating brackets available in the market, which are composed of different materials such as polycarbonate and ceramics 3 , 4 . The great advantage of these materials regarding metallic brackets is esthetics 5 .…”
Section: Introductionmentioning
confidence: 99%